A novel Nafion‐Functionalized Polyethersulfone(PES)‐based ion‐permselective separator for high performance Li‐O2 batteries using LiI as a redox mediator. (11th August 2022) - Liu, Jiuqing; Song, Feifei; He, Junying; Hong, Zikun; Li, Qihou; Chen, Ya; Bai, Lishun; Zeng, Fanli; Cheng, Chen; Chen, Zehao
Summary: Owing to its unparalleled theoretical energy density, the Li‐O2 batteries are thought to be one of the most promising energy storage systems, but its application is seriously hindered by its potential safety risks arising from the passivation and corrosion of lithium anode. To address these issues, it is an efficient way to develop functionalized separator that could prevent the migration of anions and macromolecules from cathode toward anode. Herein, a novel Nafion‐functionalized polyethersulfone (PES)‐based ion‐permselective separator was prepared by using non‐solvent induced phase separation (NIPS) method. The Nafion ensures a better physical strength of the composite separator, and further characterizations show that the obtained composite separator owns good ionic conductivity (0.52 mS cm −1 ), high lithium ion migration number (0.80), and better cyclic stability (120 cycles, 1000 mAh g −1 ). Consequently, the composite separator serves as an excellent candidate to solve the "shuttle effect" of redox mediators (RMs), the assembled Li‐O2 battery with composite separator adding LiI as RMs presents lower charge overpotential and longer cycle stability (170 cycles, 1000 mAh g −1 ). Abstract : A novel PES‐based Nafion‐filled composite polymer separator was developed by us. Attributing to Nafion filling, a high lithium ion migration number (0.80) was achieved. The separator shows positive effect on inhibiting the shuttle activity of RMs, the Li‐O2 battery using Nafion‐filled separator, and LiI as RMs presents ultra‐long cycle performance (170 cycles, 1000 mAh g −1 ). This work provides a new perspective for the development of functional polymer separator for Li‐O2 battery containing RMs.